Structural and electronic insight into the effect of indium doping on the photocatalytic performance of TiO2 for CO2 conversion. Issue 11 (11th November 2021) - Reñones, Patricia; Fresno, Fernando; Oropeza, Freddy E.; Gorni, Giulio; de la Peña O'Shea, Víctor A.
Abstract : In-doping induces electronic modifications in TiO2 leading to an increase in the CO2 photoreduction selectivity towards CH4 . Abstract : The photocatalytic conversion of CO2 to fuels and useful chemicals is a valuable artificial photosynthesis approach that simultaneously addresses the valorization of CO2 emissions and the storage of solar energy. In this work, we show how indium doping influences the activity and selectivity of TiO2 as a CO2 reduction photocatalyst using water as the electron donor, and how silver nanoparticles deposited on the semiconductor surface reinforce these effects, leading to promising photocatalytic systems with enhanced performance. For that purpose, catalysts with different indium contents have been synthesized by a simple wet chemical method starting from anatase TiO2, and a selected In-doped sample has been further modified by silver decoration following an impregnation method. The catalysts have been thoroughly characterized using different physicochemical techniques and tested for UV photocatalytic CO2 conversion in a laboratory-made, continuous flow gas-phase reaction system. Characterization results point at a substitutional doping of indium into the anatase crystal structure, as inferred from the absence of additional phases visible by X-ray diffraction as well as Raman and UV-vis spectroscopy, and further supported by an expansion of the unit cell volume calculated from XRD profile refinement and ratified by DFT calculations, and the absence of In–In scattering in EXAFS spectra. This substitution does not modify the optical band gap of the synthesized catalysts but, according to XPS, theoretical calculation and fluorescence spectra, induces electronic modifications that reduce the n-type character and the electron–hole recombination rate. In-doped catalysts show an increased selectivity towards the highly reduced product CH4 in photocatalytic CO2 reduction tests, whereas the main product attained with undoped titania is CO. Silver decoration, which leads to the initial formation of silver oxides that are reduced to metallic Ag nanoparticles under the UV light used in the reactions, dramatically reduces electron–hole recombination and further enhances the selectivity to methane and ethane in CO2 photocatalytic conversion.